Floratorium - Oppenheim, Joanne; Schindler, S. D. (New York : Bantam Books, 1994)
Uses a tour through a botanical museum to introduce many different kinds of plants and the ways in which they grow all over the world.
"A Byron Preiss book."
"With a full-color Floratorium wall poster inside!"--Cover.
Includes index.
Keywords: Botanical museums -- Juvenile literature; Plants; Botany; Botanical museums